2004
DOI: 10.1023/b:ddas.0000043390.12150.8b
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Administration of Topical Glutamine Enhances the Capability of the Rat Colon to Resist Inflammatory Damage

Abstract: Glutamine is an important nutrient for the GI tract and has been shown to exert a protective effect on the bowel. Nonetheless, in the context of IBD, data demonstrating a therapeutic role for glutamine has been inconclusive. IBD is associated with oxidative stress caused by reactive oxygen species. We aimed to investigate the effect of topical glutamine administration in rats before or after induction of colitis by trinitrobenzenosulfonic acid. In study I glutamine enemas were given beginning 2 days before or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…8 In IBD patients, protein composition such as glutamine enrichment does not influence the effectiveness of enteral nutrition, 9 but studies are still limited. In animals, glutamine protects intestinal mucosa in different models of IBD, i.e., trinitrobenzene sulfonic acid (TNBS), [10][11][12] dextran sulfate sodium (DSS), 13 indomethacin, 14,15 or acetic acid 16 -induced intestinal inflammation. In TNBS-induced colitis, prophylactic treatment (2 weeks) with glutamine decreased bacterial translocation, intestinal lesions, and cytokine (TNFa, IL-8) production.…”
Section: Glutaminementioning
confidence: 99%
See 2 more Smart Citations
“…8 In IBD patients, protein composition such as glutamine enrichment does not influence the effectiveness of enteral nutrition, 9 but studies are still limited. In animals, glutamine protects intestinal mucosa in different models of IBD, i.e., trinitrobenzene sulfonic acid (TNBS), [10][11][12] dextran sulfate sodium (DSS), 13 indomethacin, 14,15 or acetic acid 16 -induced intestinal inflammation. In TNBS-induced colitis, prophylactic treatment (2 weeks) with glutamine decreased bacterial translocation, intestinal lesions, and cytokine (TNFa, IL-8) production.…”
Section: Glutaminementioning
confidence: 99%
“…10 A shortterm (3-day) prophylactic treatment also limited TNBSinduced intestinal damage. 11,12 Curative treatment with oral glutamine also demonstrated a beneficial effect in an indomethacin model, 14 but failed in a TNBS model. 11,17 These experimental data suggest a beneficial role of glutamine during colitis that could be explained by different mechanisms, summarized in Figure 1.…”
Section: Glutaminementioning
confidence: 99%
See 1 more Smart Citation
“…14 Because enteral glutamine is the main source of amino acids for the enteral mucosa and is metabolized at high rates by enterocytes and immunocytes, 15,16 it has been used in many clinical conditions such as extended trauma or burning, and prolonged fasting and chemotherapy to prevent enteritis and colitis. 17 Although it has been found that glutamine supplementation has no clear benefit in patients with IBD, 18 and there is a report that glutamine enemas fail to improve the inflammatory response in animals receiving TNBS, 19 administration of glutamine by gastric gavage 20,21 or enema 22 before TNBS instillation reduces colonic damage in animals with experimental colitis. Moreover, we have previously reported that glutamine prevents NF-B activation in rats with acetic acid-induced colitis, 1 and it has been recently shown that dietary glutamine improves mucosal function in a dextran sulfate sodium (DSS)-induced model of experimental colitis.…”
mentioning
confidence: 99%
“…24 and 46). Animal studies of Gln supplementation also suggest gut mucosal cytoprotective effects of this amino acid in chemically-induced IBD, which is associated with increased local cytokine production and (15,18) and accelerated epithelial cell apoptosis (16). Few studies have examined the impact of Gln-derived nucleotides and/or their derivatives themselves on the prevention of intestinal epithelial cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%